EFISIENSI LOGISTIK DAN DISTRIBUSI UNTUK OPTIMALISASI METODE TRANSPORTASI PUPUK DI PROVINSI RIAU: EFISIENSI LOGISTIK DAN DISTRIBUSI UNTUK OPTIMALISASI METODE TRANSPORTASI PUPUK DI PROVINSI RIAU - Melliana, Melliana; Azmi, Azmi; Wiroto, Noto; Fitra, Fitra; Mesra, Trisna; Novri, Novri; Febriyansyah, Febriyansyah; Rihas, Sabila Nur (Komunitas Manajemen Kompetitif, 2025)
Efficient fertilizer distribution is an urgent need for farmers in Riau Province to ensure optimal agricultural production. The main problem faced by the partner community is the high transportation cost caused by ineffective distribution routes. The purpose of this community service activity is to provide managerial and technical solutions in fertilizer distribution using transportation methods, namely North West Corner (NWC), Least Cost Method (LCM), and optimization with the Stepping Stone Method. The implementation method includes socialization, training, application of calculations to real partner cases, and mentoring in interpreting the results of method comparisons. The results show that the LCM method produces lower distribution costs compared to NWC, and further optimization using the Stepping Stone method leads to even more efficient distribution costs. This activity not only provides direct benefits to the partner in the form of increased logistical efficiency and cost savings but also contributes to the development of knowledge in the field of education, particularly in the teaching of logistics optimization and distribution management through applied research. Thus, this community service program creates a dual impact: enhancing partner capacity in practice while also providing a practical learning model for students and academics to apply transportation optimization theory to real-world problems.